The RAD7 and RAD16 genes, which are essential for pyrimidine dimer removal from the silent mating type loci, are also required for repair of the nontranscribed strand of an active gene in Saccharomyces cerevisiae. - Verhage, R (Mol Cell Biol, 1994)
The rad16 mutant of Saccharomyces cerevisiae was previously shown to be impaired in removal of UV-induced pyrimidine dimers from the silent mating-type loci (D. D. Bang, R. A. Verhage, N. Goosen, J. Brouwer, and P. van de Putte, Nucleic Acids Res. 20:3925-3931, 1992). Here we show that rad7 as well as rad7 rad16 double mutants have the same repair phenotype, indicating that the RAD7 and RAD16 gene products might operate in the same nucleotide excision repair subpathway. Dimer removal from the genome overall is essentially incomplete in these mutants, leaving about 20 to 30% of the DNA unrepaired. Repair analysis of the transcribed RPB2 gene shows that the nontranscribed strand is not repaired at all in rad7 and rad16 mutants, whereas the transcribed strand is repaired in these mutants at a fast rate similar to that in RAD+ cells. When the results obtained with the RPB2 gene can be generalized, the RAD7 and RAD16 proteins not only are essential for repair of silenced regions but also function in repair of nontranscribed strands of active genes in S. cerevisiae. The phenotype of rad7 and rad16 mutants closely resembles that of human xeroderma pigmentosum complementation group C (XP-C) cells, suggesting that RAD7 and RAD16 in S. cerevisiae function in the same pathway as the XPC gene in human cells. RAD4, which on the basis of sequence homology has been proposed to be the yeast XPC counterpart, seems to be involved in repair of both inactive and active yeast DNA, challenging the hypothesis that RAD4 and XPC are functional homologs. IMAGES: